Reviewing open kitchen concept regarding its effect on motivation of chefs - Sırıklı, İsmet Kutay; Seçim, Yılmaz (Anais Brasileiros de Estudos Turísticos, 2024)
The open kitchen concept has been evaluated from the perspective of chefs in quite a few studies. Further research is necessary to investigate the impact of chefs' working conditions in open kitchens on their professional development, motivation, and work processes. This study aims to understand the impact of open kitchen working experiences on chefs who have previously worked in closed kitchens. Specifically, it examines how these experiences affect their mood, motivation, and creativity in the kitchen. For the research, twenty five chefs working in Michelin Starred restaurants in Turkey were interviewed with semi-structured questions. The answers were deciphered through descriptive analysis. The results show that the chefs responded positively to working in open kitchens. Chefs are motivated, happy, self-confident and satisfied while working. Working in front of customers causes them to be more careful, attentive, clean and self-confident. Customers follow the chefs in the restaurant with interest, wonder how the dishes are made and want to learn. This interaction of customers positively affects the chefs' work. Finally, the interaction between the chefs has positive results. The chefs exercise caution in their communication with customers, avoiding colloquial language, profanity, and insulting expressions. More importantly, this leads to the cessation of patriarchal behaviors. As a result, the open kitchen concept application is recommended to the enterprises since the motivation and satisfaction of the chefs will be a factor that will strengthen their professional development, recognition in the restaurant and the popularity of the kitchen will strengthen their professional ties.